2015
DOI: 10.1007/s11262-015-1257-y
|View full text |Cite
|
Sign up to set email alerts
|

Porcine epidemic diarrhea virus ORF3 gene prolongs S-phase, facilitates formation of vesicles and promotes the proliferation of attenuated PEDV

Abstract: Porcine epidemic diarrhea virus (PEDV) is a porcine enteropathogenic coronavirus that has received increasing attention since the emergence of a PEDV variant worldwide. Previous studies have shown that PEDV ORF3 encodes an ion channel protein. However, its influence on cell cycle and subcellular structure still require more research. In this study, we developed a Vero cell line that stably expresses PEDV ORF3 gene. Subcellular localization and influences of PEDV ORF3 on host cells were investigated. We further… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…Porcine epidemic diarrhea virus (PEDV), the causative agent of PED, is an enveloped, positive-stranded RNA virus in the genus Alphacoronavirus, family Coronaviridae, order Nidovirales (Sato et al, 2018;Yu et al, 2018). The genome of a PEDV is approximately 28 k nt in length and is composed of seven open reading frames (ORFs) arranging in the order 5′-ORF1a/1b-S-ORF3-E-M-N-3′, which encodes four structural proteins and seventeen non-structural proteins (nsp1-nsp16, and ORF3) (Ye et al, 2015;Cheun-Arom et al, 2016). The 5′ two thirds of the genome contains two overlapping ORFs, ORF1a and ORF1b, which encode nsps that are cleaved by viral encoded proteases into 16 nsps (nsp1-16), directing genome replication, transcription, translation and viral polyprotein processing (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porcine epidemic diarrhea virus (PEDV), the causative agent of PED, is an enveloped, positive-stranded RNA virus in the genus Alphacoronavirus, family Coronaviridae, order Nidovirales (Sato et al, 2018;Yu et al, 2018). The genome of a PEDV is approximately 28 k nt in length and is composed of seven open reading frames (ORFs) arranging in the order 5′-ORF1a/1b-S-ORF3-E-M-N-3′, which encodes four structural proteins and seventeen non-structural proteins (nsp1-nsp16, and ORF3) (Ye et al, 2015;Cheun-Arom et al, 2016). The 5′ two thirds of the genome contains two overlapping ORFs, ORF1a and ORF1b, which encode nsps that are cleaved by viral encoded proteases into 16 nsps (nsp1-16), directing genome replication, transcription, translation and viral polyprotein processing (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ORF3, as the only accessory gene in PEDV, is thought to function as an ion channel and to influence virus production and virulence (Wang et al, 2012). PEDV ORF3 protein can prolong cellular S-phase, facilitate formation of vesicles and thus promote the proliferation of attenuated PEDV rather than virulent PEDV (Ye et al, 2015). Previous study demonstrated that ORF3 and S are co-localized in several cellular compartments in infected cells, and ORF3 may interact with S during PEDV assembly and consequently exert its activity at this step of virus replication (Kaewborisuth et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The PEDV S protein is a key factor that mediates the entry of PEDV into host cells by binding to aminopeptidase N and/or glycan receptors through an unknown mechanism, thereby initiating the fusion of the virus envelope with the host cell membrane and the subsequent infection cycle (He et al, 2005;Ye et al, 2015). Thus, the S glycoprotein is the primary target for the development of vaccines against PEDV, as well as for understanding the genetic relationships between different strains and the epidemiological status of PEDV in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the structural proteins, little is known about the functions of the accessory proteins. The ORF3 gene, which is the only accessory gene, encodes an ion channel protein that regulates virus production , and it has been suggested to be an important virulence determinant (Ye et al, 2015). A previous report suggested that piglets that were inoculated orally with the wild-type CV777 strain became sick and developed severe diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…ORF3 encoded genes are not required for CoV growth in cell culture, although virus yield could be increased in their presence (Ye et al, 2015; Zhang et al, 2014b). A common feature between HCoV-229E, TGEV and PEDV is that cell-adapted strains tend to modify ORF3 (Fig.…”
Section: Viral Proteins As Virulence Factorsmentioning
confidence: 99%